Effect of caffeic acid phenethyl ester and Ankaferd Blood Stopper® on palatal wound healing in the diabetic rats - Mehmet Gul; Ahmet Günay (Wolters Kluwer Medknow Publications, 2020)
Background/Aim: Caffeic acid phenethyl ester (CAPE) and Ankaferd Blood Stopper® (ABS) are thought to contribute to wound healing. The aim of this study is to investigate the effect of ABS and CAPE on the secondary wound healing of oral mucosal tissue. Materials and Methods: A total of 63 male Sprague-Dawley rats were used in the study. Rats were randomly divided into three groups: ABS group, CAPE group, and control group. Healthy 63 rats were intraperitoneally injected with streptozotocin (Sigma Chemical Co., St. Louis, MO) 50 mg/kg in 0.2 ml 10 m citrate solution. After a week, if the blood glucose value of the rat is ≥250 mg/dl, the rats are considered to be diabetic. General anesthesia of the rats was conducted with intramuscular ketamine (8 mg/100 g). The excisional palatal wound was formed by using a 4 mm punch biopsy tool. Topical ABS was applied to ABS groups; topical CAPE application was applied to CAPE groups. Animals were sacrificed at 7, 14, and 21 days. The palatal specimens were painted with hematoxylin and eosin. The Mann-Whitney U test was used for comparison of the two groups. Results: The results of the statistical analysis determined the vessel dilatation and hemorrhage to be significantly lower in the diabetic ABS and CAPE group than the control group at 7, 14, and 21 days (P < 0.05). Conclusions: In the present study, it is concluded that ABS and CAPE have a positive effect on the wound healing process.